Advanced methodological approach in determination of the heart rate deflection point: S.Dmax versus L.Dmax methods - Siahkouhian, M.; Meamarbashi, A. (The Journal of Sports Medicine and Physical Fitness, 2013)
Aim: The aim of the present study was to compare determined heart rate deflection point (HRDP) by the long distance maximum (L.Dmax), short distance maximum (S.Dmax) and plasma lactate measurements as criterion. Methods: Fifteen healthy and active male volunteers, aged 20-24, were selected as subjects and performed the exhaustive testing protocol which took place on a calibrated electronically braked cycle ergometer. To determine the HRDP, each subject`s data was recorded during the exercise test and analyzed by a designed computer program. Venous blood samples were drawn for the measurement of plasma lactate concentration by a direct method. Results: Downward inflection of HRDP was noticed in all subjects. Comparison of the S.Dmax and L.Dmax methods with the criterion method (lactate method) showed that while HRDP determined by the S.Dmax and lactate methods were not significantly different (167±8.83 vs. 168±8.17 b/min; P=0.86), significant difference emerged between determined HRDP by the L.Dmax and lactate methods (167±8.83 vs. 139.56±6.73 b/min; P£0.001). Bland-Altman plots revealed a good agreement between S.Dmax and lactate methods (95% CI=-5 to +3.6 b/min), while there is no agreement between L.Dmax and lactate method (95% CI=+4.9 to +71.3 b/min). Significant correlation was observed between the criterion and S.Dmax model (r=0.944) whereas there was no significant correlation between the criterion and L.Dmax model (r=0.158). Conclusion: Based on these results, it could be suggested that S.Dmax method is an accurate and reliable alternative to the cumbersome, expensive, and time-consuming lactate method.